Hamadab, Sudan - Nowotnik, Ulrike; Wolf, Pawel; Hof, Catharine (e-Forschungsberichte des DAI, 2017)
The riverine town of Hamadab (3rd century BC to 4th century AD) provides in-situ findings on a large scale, representing a yet unparalleled example of urban settlement in the Middle Nile valley. The plan of a Meroitic town site allows us to study its urban development and to put its building types, construction techniques and artefact assemblages into context. Upon the successful conclusion of a 6-year funding program by the German Research Foundation, this report summarises our present knowledge on the spatial organisation and the living conditions within this sub-Saharan town.